Optimalisasi Peran Laboratorium Akuntansi dalam Penguatan Kapasitas Keuangan UKM Lokal Berbasis Kearifan Lokal dan Berkelanjutan Usaha - Masyhuri Masyhuri; Andi Tahir; Syahru Ramadan; Ahmad Fadhil; Muh Hamzah; Eslam Amir Mohammed Abdelrahman (GUYUB: Journal of Community Engagement, 2026)
The urgency of this community service lies in the practical need of local SMEs for structured and applicable assistance in preparing sustainable financial reports. This program was conducted with Family Silk Wajo and Songkok Recca Syafira Bone SMEs, which possess strong local economic potential but lack optimal financial management practices. The objective was to enhance financial management capacity through the optimization of the Accounting Laboratory of IAIN Bone as a community service and assistance center. The study employed a Community-Based Research (CBR) approach, including needs assessment, adaptive module development, and direct mentoring. The results demonstrate measurable improvements: (1) transaction recording completeness increased from 45% to 85%, (2) accuracy of transaction classification improved from 40% to 75%, and (3) the ability to prepare simple financial statements rose from 30% to 80%, as measured through pre-test and post-test evaluations and analysis of financial records. Furthermore, both SMEs were able to independently prepare consistent monthly financial reports during the mentoring period. Additional impacts include improved financial administration and the availability of periodic reports for business evaluation. However, consistency in recording practices still requires further assistance to ensure sustainability and higher-quality bookkeeping practices.